TREATMENT OF PYOMETRA IN FEMALE DOGS USING PROSTAGLANDIN F2α ± ANTIPROGESTIN (MIFEPRISTONE) - SHAH, M A; PANDE, N; SHAH, I A; AGRAWAL, R; SHARMA, U; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2016)
The female dogs confirmed for pyometra by history, clinical examination, ultrasonography and blood samplingwere subjected to prostaglandin F2α (PGF2α) therapy with or without mifepristone, an antiprogestin (n=6 in eachgroup). Following treatment, 11 out of 12 animals were successfully treated and recurrence till next estrous cycle wasobserved only in one case. The clinical signs uterine diameter and hemato-biochemical parameters were normalizedby day 14 post onset of treatment in both the groups (p
Keywords: Canine; Dog; Mifepristone; PGF2α,; Pyometra